Protein-protein interactions between RUNX3 and ZEB1 in chronic lung injury induced by methamphetamine abuse - Bao, Ning; Cheng, Lin; Wang, Yun; Peng, Zhe; Wang, Zhengkun; Chen, Shuangquan (Frontiers in Pharmacology, 2022)
Methamphetamine (MA) is the most common addictive drug for abuse. Runt-related transcription factor 3 (RUNX3) and zinc finger E-box-binding homeobox 1 (ZEB1) have been confirmed to be related to lung inflammation and fibrosis. But it remains unclear if there exist the protein-protein interactions (PPIs) between RUNX3 and ZEB1 and if this PPIs are involved in MA-induced chronic lung injury. In this study, lung injury was evaluated by Echocardiography, HE staining and Western blots. The viability of alveolar epithelial cells (AECs) was detected by cell counting kit-8 (CCK-8). MOE software, String database, Co-immunoprecipitation (Co-IP) and confocal immunofluorescence were used to predict and identify the PPIs between RUNX3 and ZEB1. AEC were treated with siRNA for knockdown. It was found that chronic exposure to MA led to the increase in peak blood flow velocity of the pulmonary artery (PV) and the acceleration time of pulmonary artery blood flow (PAT), and caused the adhesion and fusion of the alveolar walls along with the altered activity of AECs. MA decreased RUNX3, and increased ZEB1 and their downstream signals. PPIs between RUNX3 and ZEB1 were identified, and the protein binding rate of RUNX3-ZEB1 was increased in MA-induced lung injury. Therefore, there exist the interactions between RUNX3 and ZEB1, RUNX3 was protective against lung injury, but ZEB1 and the PPIs between them were disruptive in chronic lung injury induced by MA. It provides a new therapeutic target for MA abuse-induced chronic lung injury.